THE EFFECT OF GENERATIVE LEARNING MODEL TO THE ANALYSIS ABILITY OF STUDENT IN HUMAN SYSTEM MATERIAL - Hapida, Yustina; Faizah, Ulul; Fitriyanti, Ovi; Nawawi, Sulton (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
This study aims to determine the effect of generative learning model on theability of student analysis on matter of human nervous system at XI IPA class at Musi Rawas. This research uses quasi experiment method of non-equivalent control groupdesign. The research population is the students of XI IPA class with sampling technique using non probability of purposive sampling. Based on the analysis result, it shows that the mastery in the experimental class is 67,7% higher than the control class that is 55,3%. The improvement of analytical ability can be seen from the value of N-gain with the experimental class has a value of N-gain of 0,53 and the control class is 0,19 with low category. The results of hypothesis testing using t-test obtained by value tarithmetic =3,969 and ttable =1,670 confidence level of 95%, ( = 0,05). The data shows that t arithmetic >t table , then H0 is rejected and Ha is accepted. Therefore, it can be concluded that the generative learning model has an effect on the students' analysis ability at XI IPA class.Keywords: analytical skills, nervous system,generative learning